The fixed stars - Wizenberg, Molly (Abrams Press, 2020)
At age 36, while serving on a jury, author Molly Wizenberg found herself drawn to a female attorney she hardly knew. Married to a man for nearly a decade and mother to a toddler, Wizenberg tried to return to her life as she knew it, but something inside her had changed irrevocably. Instead, she would discover that the trajectory of our lives is rarely as smooth or as logical as we<U+2019>d like to believe. Like many of us, Wizenberg had long understood sexual orientation as a stable part of ourselves: we<U+2019>re “born this way.” Suddenly she realized that her story was more complicated. Who was she, she wondered, if something at her very core could change so radically? The Fixed Stars is a taut, electrifying memoir exploring timely and timeless questions about desire, identity, and the limits and possibilities of family. In honest and searing prose, Wizenberg forges a new path: through the murk of separation and divorce, coming out to family and friends, learning to co-parent a young child, and realizing a new vision of love. The result is a frank and moving story about letting go of rigid definitions and ideals that no longer fit, and learning instead who we really are.